2022
DOI: 10.51253/pafmj.v72isuppl-3.9535
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Brain and Neck Neoplasms among Interventional Cardiologists; A Multicenter Study

Abstract: Objective: To determine the prevalence of brain and neck neoplasms among Interventional Cardiologists. Study Design: Analytical Cross-sectional study. Place and Duration of Study: Department of Cardiology/Interventional Cardiology of two Tertiary Cardiac Care Centers of Rawalpindi and Lahore Pakistan from Mar 2021 to Apr2022. Methodology: By using the non-probability, consecutive sampling technique, fifty Interventional Cardiologists’ (n=50) of both genders between 35-75 years of age, working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The multi-centre study in Pakistan reported a 2% prevalence of head and neck malignancy in a sample of 50 interventional cardiologists who had worked for more than 10 years. (16) The side involved in the identified head and neck tumour was not specified. The doses recorded by personal radiation monitoring devices (PRMD) were not mentioned as part of the data collection.…”
Section: Resultsmentioning
confidence: 99%
“…The multi-centre study in Pakistan reported a 2% prevalence of head and neck malignancy in a sample of 50 interventional cardiologists who had worked for more than 10 years. (16) The side involved in the identified head and neck tumour was not specified. The doses recorded by personal radiation monitoring devices (PRMD) were not mentioned as part of the data collection.…”
Section: Resultsmentioning
confidence: 99%